Complimentary Discrimination and Complementary Discrimination in Faculty Hiring - Angela Onwuachi-Willig (Washington University Law Review, 2010)
This Article focuses on one form of discrimination in faculty hiring. Specifically, this Article concentrates on discrimination against the “over qualified” minority faculty candidate, the candidate who is presumed to have too many opportunities and thus gets excluded from faculty interview lists and consideration. In so doing, this Article poses and answers the question: “Can exclusion from interviewing pools and selection based upon the notion that one is just ‘too good’ to recruit to a particular department constitute an actionable form of discrimination?” Part I of this Article begins by briefly reviewing the changes in faculty diversity and inclusion at colleges and universities. Part II lays out a hypothetical of a superstar, bidding-war minority faculty candidate in English and explicates how the exclusion of this candidate, although accompanied by high praise and not racial animus, may constitute actionable discrimination. In so doing, it examines how federal courts have analyzed the concept of “overqualification” when employers have articulated it as the reason for not hiring a job applicant in discrimination lawsuits. It then explains why the myth of the “overqualified” minority faculty candidate as the “highly sought-after” candidate can render that candidate's exclusion from interviews, and thus hiring, a unique and specific form of racial discrimination. Part III further explicates how this form of “complimentary discrimination” works to create the “complementary discrimination” of keeping other “less qualified,” but certainly qualified minorities locked out of the academic market or out of particular schools. Specifically, it explains how faculties' dreams of one day recruiting the superstar minority candidate—generally the only type of minority candidate whom they truly find acceptable—can function as an excuse for not “settling” for racial minority candidates who are well qualified, but not as highly credentialed as the superstars, which, in turn, continues the cycle of low representation of minorities on college and university faculties. To illustrate this point, this Part details a hypothetical involving a minority female candidate on the entry level market in law. The Conclusion of this Article then expresses and details the need for and importance of increasing diversity on college and university faculties in today's society and the importance of carefully evaluating one's own biases when creating and serving on faculty search committees.
Keywords: Diversity in the workplace; Discrimination in employment; College teachers